The North Atlantic market for air freight, with projections for 1965, 1970, and 1975 : summary edition - Brewer, Stanley H.; Rosenzweig, James Erwin, 1929- joint author.; Kast, Fremont Ellsworth, 1929- joint author.; University of Washington. College of Business Administration. (Seattle : College of Business Administration, University of Washington, 1962)
Mode of access: Internet.